Hemorrhage after pancreaticoduodenectomy: does timing matter?. Issue 10 (October 2016) - Kasumova, Gyulnara G.; Eskander, Mariam F.; Kent, Tara S.; Ng, Sing Chau; Moser, A. James; Ahmed, Muneeb; Pleskow, Douglas K.; Callery, Mark P.; Tseng, Jennifer F.
Abstract: Background: Hemorrhage after pancreaticoduodenectomy is a potentially fatal complication. We retrospectively reviewed state-wide data to evaluate incidence, type of hemorrhage, treatment modalities, and outcomes. Methods: Healthcare Cost and Utilization Project's Florida State Inpatient Database was queried 2007–2011 for patients undergoing pancreaticoduodenectomy. Characteristics and outcomes were compared by χ 2 . Multivariate logistic regression model was generated for risk of hemorrhage during index visit. Results: Of 2548 patients, 217 (8.5%) developed post-operative hemorrhage during their index visit with 139 (64.0%) requiring angiographic, endoscopic, or operative intervention. Overall mortality during index visit was 5.7% (146) – significantly higher in those patients who had post-operative hemorrhage (24.9%) vs not (4.0%) (p < 0.0001). Mortality was significantly higher when post-operative hemorrhage occurred during the second (POD 8–14) vs first (POD 0–7) week at 15/28 vs 16/74, respectively (p = 0.007). On multivariate analysis, male sex (OR 1.56, p = 0.003), vascular resection (OR 1.88, p = 0.017), very low hospital volume (≤7 PD/year; OR 1.62, p = 0.016), and post-operative intra-abdominal/wound infection (OR 2.31, p < 0.0001) were independent predictors for risk of hemorrhage during index visit. Conclusions: Hemorrhage following pancreaticoduodenectomy remains common, resulting in significantly increased mortality. Hemorrhage during the second post-operative week carries approximately double the mortality of early bleeding, suggesting different etiologies requiring differing treatment approaches.